2018
DOI: 10.1002/smi.2812
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pet therapy on the physiological and subjective stress response: A meta‐analysis

Abstract: Studies have reported that exposure to pet therapy (PT) can reduce physiological and subjective stress and anxiety levels. The aim of this meta-analysis is to examine the efficacy of PT as a method for reducing physiological stress levels (blood pressure and heart rate) and subjective stress and anxiety scores (self-reported stress/anxiety). Further, we examined the effects of sample characteristics and modifications to the PT (different age groups and health status of participants across samples, whether a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 42 publications
5
47
3
1
Order By: Relevance
“…Despite these divergent findings, human-animal interactions have been consistently shown to reduce subjective and physiological stress levels (for a meta-analysis, see Ein et al [10]), function as social support and enhance social interactions (for a review, see Beetz et al [11]) and to decrease depressive symptoms (for meta-analyses, see Borgi et al [12], and Souter and Miller [13]). This leads to the hypothesis that pet ownership might also have beneficial effects on individuals working in high-risk occupations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these divergent findings, human-animal interactions have been consistently shown to reduce subjective and physiological stress levels (for a meta-analysis, see Ein et al [10]), function as social support and enhance social interactions (for a review, see Beetz et al [11]) and to decrease depressive symptoms (for meta-analyses, see Borgi et al [12], and Souter and Miller [13]). This leads to the hypothesis that pet ownership might also have beneficial effects on individuals working in high-risk occupations.…”
Section: Introductionmentioning
confidence: 99%
“…Relationships with our companion dogs not only bring us joy, but science has also demonstrated that even brief positive interactions with dogs can decrease human stress and anxiety. 1 For children living in a home with a dog, the benefits include increased responsibility and compassion, a sense of security and pride, and even positive impacts to the immune system. Potential risks of living with a dog, however, also exist-especially for the most vulnerable, younger, family members.…”
mentioning
confidence: 99%
“…Both shortterm and longterm options have been shown to be effective for help ing undergraduate and graduate students deal with stress and related disorders (Huang, Nigatu, SmailCrevier, Zhang, & Wang, 2018;Yusufov, NicoloroSantaBarbera, Grey, Moyer, & Lobel, 2018). Some effective therapies for stress in gen eral and psychological disorders specifically have employed the assistance of a variety of animals (Ein, Li, & Vickers, 2018). Many different populations interact with therapy animals including children, adolescents, adults, and older adults, people with physical ailments, people needing speech therapy, people with psychological disorders, and people with developmental disabilities (Boyer & Mundschenk, 2014;Braun, Stangler, Narveson, & Pettingell, 2009;Fedor, 2018;Matuszek, 2010;Nimer & Lundahl, 2007).…”
Section: Helping Adults Cope With Stress: Animal-assisted Therapymentioning
confidence: 99%